Economic Analysis of the Law on Execution of Fiduciary Guarantees After the Constitutional Court Decision - Mulyani, Sri; Irianto, Sigit; Erwin Isharyanto, Johan; Idris, Kholik; Santoso, Budi; Fahrurrozie Hidayat, Arief; Akkapin, Supaphorn (PT. Multidisciplinary Press Indonesia, 2024)
Under Article 29(1) of Law No. 42 of 1999 on Fiduciary Guarantees (UUJF), the execution of fiduciary collateral objects may only proceed through an executorial title. Creditors, as holders of fiduciary collateral certificates, possess the right to directly execute the collateral if the debtor defaults, as stipulated in Article 15 paragraphs 2 and 3 of the UUJF. This provision formed the basis for a debtor’s petition to the Constitutional Court, resulting in Decision No. 18/PUU-XVII/2019, which favored the debtor by mandating that creditors must execute collateral through the court rather than directly. Subsequently, creditors appealed, leading to Decision No. 2/PUU-XIX/2021, which allowed execution through the District Court as an alternative. This research explores the economic analysis of these legal changes, addressing two primary questions: (1) How does economic analysis of law apply to the execution of fiduciary collateral post-Constitutional Court rulings? (2) Can fiduciary collateral execution be effectively carried out under the Constitutional Court’s decisions? Utilizing Richard A. Posner’s economic analysis of law framework, this empirical normative study employs qualitative methods to assess statutory and case law. The findings indicate that Decision No. 2/PUU-XIX/2021 aligns more closely with economic efficiency compared to Decision No. 18/PUU-XVII/2019. However, the inconsistency between these rulings increases costs and legal uncertainty, adversely affecting the broader economy by complicating credit facilities for businesses.